Placental Growth Factor as a Predictor of Severity of Preeclampsia in Iraqi Women - Alshihabi, Radhia A.; Alsaadi, Yasmin L. (Iraqi Journal of Science, 2025)
Pre-eclampsia is a serious pregnancy complication marked by high blood pressure, typically exceeding 140/90 mmHg, that often emerges after the 20th week of pregnancy. It may be pronounced if there is a high risk for the mother or fetus. The importance of the placental growth factor (PlGF) in predicting preeclampsia has been established by earlier research. However, the study aims to evaluate the predictive accuracy of serum Placental growth factor in determining the severity of disease. The study involved 90 pregnant Iraqi women who developed preeclampsia after 24 weeks of gestation. Based on the magnitude of their hypertension biochemical parameters and, other symptoms, the women were categorized into two groups: 45 moderate cases and 45 severe cases. They were aged between 27-29 years and were selected from the Al-Elwiya Teaching Hospital for Maternity from April to June 2024. Both blood pressure and proteinuria were assessed. Furthermore, a blood sample was obtained from each patient in order to evaluate the serum levels of PlGF using ELISA in addition to hematological and biochemical parameters. The severe PE group exhibits a statistically significant (p≤0.05) increase in both systolic and diastolic blood pressures when compared to the moderate group. Moreover, there is a statistically significant (P≤0.01) difference in platelet count, Aspartate amino Transferase (AST), Alanine amino Transferase (ALT), serum Creatinine and blood urea between the PE groups. In severe cases of PE, the presence of proteinuria on the urine dipstick at a level of 2+ or higher was found to be highly significant (P≤0.01) when compared to moderate cases. Notably, PlGF levels showed no significant variation between the different pre-eclampsia groups. This is not surprising, given that pre-eclampsia is a complex condition that affects multiple systems, making it challenging to accurately predict the severity of the disease. The results indicate PlGF is unable to differentiate between cases of moderate and severe PE. Further investigation is required to determine the predictive efficacy of PlGF in relation to the severity of the disease, taking into account the type of disease and gestational week.